Diagnostic Performance of Urinary Antigen Test and Molecular Method for Detection of Legionella pneumophila: A Clinical Perspective - Thanaa R. Abdulrahman; Shaymaa A. Gauad; Amar k. Muhamad; Jabbar S. Hassan (Disease and Health: Research Developments Vol. 10, 2025)
Background: Legionella pneumophila (L. pneumophila) is a gram-negative bacterium, which causes Legionnaires’ disease as well as Pontiac fever. It is an acute pneumonia caused by Legionella spp. Of the 50 species and 72 serogroups belonging to the genus Legionella, L. pneumophila serogroup one (sg1) is responsible for at least 80% of human infections. Objective: To determine the frequency of Legionella pneumophila in pneumonic patients, to determine the clinical utility of diagnosing Legionella pneumonia by urinary antigen testing (LPUAT) in terms of sensitivity and specificity, to compares the results obtained from patients by urinary antigen test with q Real Time PCR (RT PCR) using serum samples and to determine the frequency of serogroup 1 and other serogroups of L. pneumophila. Methods: A total of 100 pneumonic patients (community acquired pneumonia) were enrolled in this study during a period between October 2016 to April 2017; 92 samples were collected from patients attended and admitted to Al-Imamein Al-Kadhimein Medical City and 8 samples from those in the (Center of Kidney Diseases and Transplantation) in the Medical City of Baghdad. All patients were under therapy with antibiotics. Serum and urine specimens were obtained from all patients; urine samples were processed for urinary antigen test (rapid test). Serum samples were collected and submitted to DNA extraction for detection of L. pneumophila mip gene by q RT PCR assay. All participants were surveyed using a standard questionnaire. The statistical analysis of this prospective study was performed with the Statistical Package for Social Sciences (SPSS) 21.0 Software and Microsoft Excel 2013. Numerical data were described as mean, standard deviation, and median with 95% confidence intervals. Chi-square test or Fisher’s exact test was used to describe the association between variables. Results: The percentage of L. pneumophila in two hospitals in Baghdad was 30%. Of these, 26% were serogroup 1 detected by urinary antigen testing (UAT). On the other hand, 23% of samples were positive by q RT PCR based mip gene; of these, 19 % were serogroup 1 and 4% were another serogroup. The sensitivity of UAT is high (P value < 0.001), which means statistically highly significant than q RT PCR. Conclusion: High frequency of LD caused by L. pneumophila sg1 was observed in Iraqi patients, LPUAT is a rapid tool for early diagnosis of Legionella infection, which highlights the need of using this test in hospitals and health institutions and there is a high prevalence of L. pneumophila in Iraq that refer to the necessity of considering this microorganism point of view in future studies for detection and treatment in pneumonic patients. This study also recommended to prove the other serogroups of these bacteria be tested in Iraqi patients, rapid UAT is reliable for the diagnosis of LD in Iraqi hospitals, and serum samples should be used in the diagnosis of LD by q RT PCR.